(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Long intervals between detecting breast cancer and the beginning of treatment can influence the prognosis of the course of the disease and survival. This research aims to reveal the psychological characteristics of women with breast cancer who applied for specialized medical care late after detecting a mass lesion in the breast. The methods used in the study were a questionnaire, a test method, and methods of mathematical data processing. The Analysis of Variance (ANOVA) method was used as a method of mathematical statistics. The study involved 149 women aged 32 to 80 years (mean age 55 years) with breast cancer of different stages under the care of an oncologist from the time of diagnosis up to 6 months, living in Chelyabinsk city and Chelyabinsk region, Russia, who took part in the study in 2019-2021. Based on empirical research, it was found that women who delayed contacting their doctor to diagnose and initiate treatment of breast cancer had a more positive worldview, a more diverse repertoire of coping strategies, expressed motivational and cognitive components of personal helplessness, and an internal locus of control, compared to women who addressed their physician at the first signs of breast cancer.